2021
DOI: 10.4103/japtr.japtr_297_20
|View full text |Cite|
|
Sign up to set email alerts
|

In silico identification of natural products from Centella asiatica as severe acute respiratory syndromecoronavirus 2 main protease inhibitor

Abstract: Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) main protease (S-CoV-2 Mpro) is one of the main targets in designing antiviral against SARS-CoV-2. Centella asiatica contains several triterpenoids, polyacetylenes, and benzoic ester derivative with various biological activities including anti-inflammation and antiviral. Triterpenoids from C. asiatica could act as inhibitors of S-CoV-2 Mpro. The main objective of this study was to identify potential natural products from C. asiatica as S-CoV-2 Mpro i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Another in silico study demonstrated the interaction of madasiatic acid, asiaticoside, termolinic acid, madecassic acid, asiatic acid, with proinflammatory cytokines viz; IL-1α, IL-1β, IL-6, IL-4 and exhibited anti-inflammatory properties [ 48 ]. Antiviral properties and anti-hyperuricemic activity of isothankunic acid have been studied [ 49 , 50 ]. However, the role of isothankunic acid in antifibrotic activity is yet to be studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another in silico study demonstrated the interaction of madasiatic acid, asiaticoside, termolinic acid, madecassic acid, asiatic acid, with proinflammatory cytokines viz; IL-1α, IL-1β, IL-6, IL-4 and exhibited anti-inflammatory properties [ 48 ]. Antiviral properties and anti-hyperuricemic activity of isothankunic acid have been studied [ 49 , 50 ]. However, the role of isothankunic acid in antifibrotic activity is yet to be studied.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had reported the interaction of phytochemicals such as asiatic acid, arjunolic acid, apigenin, madecassic acid, kaempferol, luteolin, quercetin, catechin, epicatechin, nobiletin, and gallic acid present in C. asiatica with identified targets [ 9 , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ]. Very few studies have reported the cellular factors that come into play in the anti-inflammatory and anti-proliferative effects of bayogenin, terminolic acid, madasiatic acid, and isothankunic acid [ [47] , [48] , [49] , [50] ]. However, their role in antifibrotic activity is yet to be studied.…”
Section: Resultsmentioning
confidence: 99%